Prototipe Alat Pengaman Pompa Otomatis pada Kerusakan Pompa Jockey CR 5 – 20 di Sistem Hydrant di Unit Penyelenggara UPBU - Fatra, Oka; Novariski, Muhammad Samudera; Athaqiya, Hasna Fatharani; Amelinda, Hestiyana; Armando, F.X Stenly; Pratama, Sendi Arya (Jurnal Teknik Mekanikal Bandar Udara, 2023)
This design was made based on problem on the hydrant system, namely the ressure gauge shows the pressure in the hydrant system dropping from 8 bar continuously. There is damage to the pump components in the hydrant system, namely, the impeller is eroded and the seal in the implementation of the dry pump so that the jockey pump cannot provide output air pressure in the hydrant system. Therefore, a pump damage protection was made which functions to turn off the pump when it cannot circulate air for 30 seconds. In the implementation of making arduinobased tools. Arduino works when the pump is on, the flow sensor detects the presence of water or not. If the flow sensor detects no air flow within 30 seconds when the pump is running, the relay will get input and turn off the pump. When the pump is off, the LED and buzzer light up to indicate that the pump is running without dispensing water.